ANTECEDENT AND CONSEQUENCE OF SOCIAL COMPUTING BEHAVIOR FOR SOCIAL NETWORK SITES: PERSPECTIVE OF SOCIAL INFLUENCE THEORY - Abdillah, Willy (Journal of Indonesian Economy and Business, 2011)
This research is a preliminary study to develop and examine the adoption model of social computing. Research model is developed upon the Social Influence Factors, Technology Acceptance Model, and Psychosocial Dysfunction. Research design was employed online and self-administered survey questionnaire. Data of 116 samples were analysed using Partial Least Square (PLS) technique. Results suggest that proposed model has met criteria of goodness-of-fit model and indicate that identification is an antecedent of desire to involve in social network sites (SNS) and involvement in SNS predicts psychosocial dysfunction. Implications for stakeholders and further research are discussed.Keyword: social computing, social influence factors, psychosocial dysfunction, and social networking sites.